Shaping Higher Education with Students : Ways to Connect Research and Teaching - Sotiriou, Mira; Standen, Alex; Tong, Vincent C. H. (Book collections on Project MUSE., 2018)
Featuring student perspectives, the book offers academics and university leaders practical suggestions and inspiring ideas on higher education pedagogy, including principles of working with students as partners in higher education, connecting students with real-world outputs, transcending disciplinary boundaries in student research activities, connecting students with the workplace, and innovative assessment and teaching practices. Written and edited in full collaboration with students and leading educator-researchers from a wide spectrum of academic disciplines, this book poses fundamental questions about learning and learning communities in contemporary higher education.